Implementation of Cooperative Learning Model Type Group Investigation Assisted by Augumented Reality on Human Excretory System Material for Critical Thinking Skills of Smpit Bina Insan Mulia Students - Sirri Wulan (CV. ULIL ALBAB CORP, 2024)
Education is the main key to the success of a nation and plays an important role in creating quality human resources. Through education, it is expected that there will be a human achievement in improving the resources and quality of himself. One of the efforts that can be made in education is to improve the quality, effectiveness, and efficiency of learning. The research design used in this study is a non-equivalent control group design. The non-equivalent control group design consists of two groups, namely the control and experimental groups. In this design, the control and experimental groups are not randomly selected. This design is carried out on two groups, namely the control and experimental groups selected based on certain considerations. The pretest and posttest results of the experimental class and control class on the sub-indicator concluded that everything had increased. In the sub-indicator of giving induction, the experimental class experienced an increase of 38%, while the control class experienced an increase of 20%. Thus, the application of cooperative learning assisted by augumented reality can be a solution to the lack of learning media that can improve students' critical thinking skills. However, there are shortcomings, namely that there are not many augmented reality simulations that are more contextualized based on existing phenomena. The application of cooperative learning type group investigation assisted by augumented reality shows good results by increasing students' critical thinking skills as evidenced by the results of the posttest data statistical hypothesis test which gives a Sig. (2-tailed) (0.001) < the significance level (0.05).